The power to define resilience in social–hydrological systems: Toward a power‐sensitive resilience framework. (9th September 2019) - Dewulf, Art; Karpouzoglou, Timos; Warner, Jeroen; Wesselink, Anna; Mao, Feng; Vos, Jeroen; Tamas, Peter; Groot, Annemarie E.; Heijmans, Annelies; Ahmed, Farhana; Hoang, Long; Vij, Sumit; et al.
Abstract: Since the early work on defining and analyzing resilience in domains such as engineering, ecology and psychology, the concept has gained significant traction in many fields of research and practice. It has also become a very powerful justification for various policy goals in the water sector, evident in terms like flood resilience, river resilience, and water resilience. At the same time, a substantial body of literature has developed that questions the resilience concept's systems ontology, natural science roots and alleged conservatism, and criticizes resilience thinking for not addressing power issues. In this study, we review these critiques with the aim to develop a framework for power‐sensitive resilience analysis. We build on the three faces of power to conceptualize the power to define resilience. We structure our discussion of the relevant literature into five questions that need to be reflected upon when applying the resilience concept to social–hydrological systems. These questions address: (a) resilience of what, (b) resilience at what scale, (c) resilience to what, (d) resilience for what purpose, and (e) resilience for whom; and the implications of the political choices involved in defining these parameters for resilience building or analysis. Explicitly considering these questions enables making political choices explicit in order to support negotiation or contestation on how resilience is defined and used. This article is categorized under: Human Water > Water Governance. Engineering Water > Planning Water. Abstract : Power‐sensitive resilience of social–hydrological systems: five definitional questions with political implications derived from critiques of the resilience concept.